Identification and functional characterization of de novo FOXP1 variants provides novel insights into the etiology of neurodevelopmental disorder - Sollis, Elliot; Fröhlich, Henning; Rappold, Gudrun (Human molecular genetics, 2016)
Abstract. De novo disruptions of the neural transcription factor FOXP1 are a recently discovered, rare cause of sporadic intellectual disability (ID). We repor
Advance access publication date: 8 December 2015
Gesehen am 08.05.2020